Perencanaan Ulang Gedung Pusat Terpadu RSUD Sidoarjo dengan Integrasi BIM (Building Information Modelling) 5D - Muhammad Raihan Abiyyu Darmawan (Jurnal Sipil dan Arsitektur, 2025)
The purpose of construction planning is to identify various elements that can facilitate the execution of the construction project, ensure compliance with applicable standarts, functionality of the building, and cost efficiency. Construction projects often face challenges both during the planning and construction stages. With technological advancement, Building Information Modelling (BIM) has become a solution to address potential issues in the construction sector by utilizing accurate 3D modelling and systems capable of capturing and managing essensial data in integrated construction planning. In this research, BIM was used to plan the construction of the GPT RSUD Sidoarjo project. 4D and 5D simulations can be applied to high-rise buildings to ensure safety, reliability, and earthqueake resistance. Additionally, the structural design is optimized for efficiency to reduce constructions costs. Expected outcomes include the planning of building structural elements, such as foundation, beam, coloums, and slab design, 2D working drawings, 3D visuals, and project management planning, including the Budget Plan (RAB), labor allocation, construction time estimation, and technical spesifications